THROMBUS OF LEFT ATRIUM AND/OR ITS APPENDAGE IN CASE OF NONVALVULAR ATRIAL FIBRILLATION: FREQUENCY OF DETECTION AND CLINICAL RISK FACTORS - I. A. Zaigrayev; I. S. Yavelov (Атеротромбоз)
The review presents data on the frequency of thrombosis detection in the left atrium (LA and/or its appendage (LAA) in patients with non-valvular atrial fibrillation (NVAF), characterizes their connection with antithrombotic therapy and the presence of cardiovascular risk factors. It was demonstrated that thrombosis in LA/LAA is detected in 4-19% of cases. At the same time, data on thrombus frequency in LA/LAA were obtained by examination of small cohorts of patients with AF, who were subjected to transesophageal echocardiography before catheter isolation of pulmonary vein ostia, cardioversion, installation of occluders in LAA. Information about thrombosis frequency in the LA/LAA without these procedures is extremely limited. The frequency of thrombus detection in LA/LAA varies depending on the population studied, the presence of cardiovascular risk factors (diabetes mellitus, metabolic syndrome, arterial hypertension, chronic kidney disease, chronic heart failure) and peculiarities of anticoagulant therapy. CHADS2 and CHA2DS2-VASc scales do not sufficiently predict the presence of thrombus in LA/LAA. For example, at least 50% of patients with LA/LAA thrombus may have a low score on these scales and therefore the risk of heart thromboembolism will be underestimated. According to the facts, adequate anticoagulant therapy does not guarantee the absence of a thrombus in the LA/LAA. Approximately 40% of thrombotic formation cases in LA/LAA do not disappear after 1 year of antithrombotic treatment.